Effects of night feeding on SPF (Specific Pathogen Free) white egg layers under heat stress - Filizciler, M; Çerçi, IH; Tatli, P (Scientific Technical Research Council Turkey, 2002)
This experiment was conducted to determine the effects of night feeding benefiting from temperature differences between night and day in SPF (Specific Pathogen Free) white leghorn egg layers under heat stress. For this purpose, 100 SPF hens were randomly assigned to two groups. The control group was fed between 510 and 2100 and the treatment group was fed between 17(00) and 09(00). House temperature was averaged at 29.5 +/- 0.78degreesC and 22.9 +/- 0.72degreesC in the control and treatment groups, respectively. The feed and water intake of the hens were 113.60 +/- 0.75 g/day and 274.96 +/- 2.62 ml/day for the control group, and 120.09+/-1.77 g/day and 218.26+/-4.97 ml/day for the treatment group (P<0.01). Egg production was 68.46% and 76.79% in the control and treatment groups respectively (P<0.01). The percentages of cracked eggs were 6.36% and 4.90% in the control and treatment groups, respectively (P<0.05). Egg shell weight and shell thickness were higher in the treatment group than in the control group. A similar effect was determined in egg weight and specific gravity (P<0.01). Average daily weight gain of hens during the experiment was 74 g and 124 g in daytime feeding and night feeding, respectively (P<0.01). The blood hematocrit level was high (P<0.01) and serum glucose was low for hens fed at night, but total calcium was not significantly different between the groups. Serum inorganic phosphate, copper and zinc levels were not significantly different between the groups (P>0.05). Economically, night feeding made a profit of $ 408.18.
Sicak stresi altindaki SPF (Specific Pathogen Free) beyaz yumurtaci tavuklarda gece yemlemesinin etkileri
Keywords: SPF hens; heat stress; feed intake; egg production; blood parameters